2021
DOI: 10.1007/s10554-021-02411-z
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial-left ventricular angle, a new measure of left atrial and left ventricular remodeling

Abstract: We assessed the left atrial-left ventricular (LA-LV) long axis angulation value as a new measure of LA remodeling, and studied its predictors, its effect on two-dimensional LA volume (2D LAVol) estimation, and optimization techniques for 2D LAVol values. Retrospective electrocardiogram-gated coronary computed tomographic angiograms of 164 consecutive patients were reviewed. The LA–LV angle was measured in reconstructed 3-chamber views, and its predictors were determined. The LAVol measured by the area-length m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Using cardiac MRI, the concept of the angle between the LA and LV long axes (LA‐LV angle) measurement has recently been established 6 . To our knowledge only a single study has previously utilized this concept in CT imaging, concerning only volume measurements, and has found only minor differences in 2D volume calculation accuracy with respect to the LA‐LV angle 7 . Using echocardiography, atrial‐focused views have been shown to yield better LA volume estimations than traditional LV‐focused views, 8 but the determinants of this difference—such as, possibly, the LA‐LV angle—have not been known previously.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using cardiac MRI, the concept of the angle between the LA and LV long axes (LA‐LV angle) measurement has recently been established 6 . To our knowledge only a single study has previously utilized this concept in CT imaging, concerning only volume measurements, and has found only minor differences in 2D volume calculation accuracy with respect to the LA‐LV angle 7 . Using echocardiography, atrial‐focused views have been shown to yield better LA volume estimations than traditional LV‐focused views, 8 but the determinants of this difference—such as, possibly, the LA‐LV angle—have not been known previously.…”
Section: Introductionmentioning
confidence: 99%
“…6 To our knowledge only a single study has previously utilized this concept in CT imaging, concerning only volume measurements, and has found only minor differences in 2D volume calculation accuracy with respect to the LA-LV angle. 7 Using echocardiography, atrial-focused views have been shown to yield better LA volume estimations than traditional LV-focused views, 8 but the determinants of this difference-such as, possibly, the LA-LV angle-have not been known previously. Even atrial-focused views may still misrepresent true LA size due to difficulty to verify a non-foreshortened view and due to constraints regarding acoustic windows 9 -indeed, getting a 2D view aligned to the LA axis would sometimes require absurd acoustic windows through the intestine.…”
Section: Introductionmentioning
confidence: 99%